Pomen izobraževanja in usposabljanja bibliotekarjev za delo z uporabniki s posebnimi potrebami - Starman, Adrijana Biba (Knjižnica, 2011)
Purpose: The article presents the importance of education and training of librarians to serve users with special needs as perceived by students of library and information science (LIS) and by students and graduates with special needs in the role of library users. Methodology/approach: Surveys amongst the 3rd year students of Librarianship and Information Science (bachelor's degree) at the Faculty of Arts (University of Ljubljana) as well as half structured interviews with 12 students and graduates with special needs as library users have been conducted. The acquired data were then analyzed and compared. Results: The results show a high level of motivation of LIS students for working with users with special needs as well as the desire for additional education and training. Comparisons of data indicate differences in understanding users with special needs, thus confirming the need for further education and training of librarians. Research limitation: Small sample size and inability to generalize the findings. Originality/practical implications: The first study in Slovenia dealing with the significance of education and training of librarians to work with users with special needs.
Keywords: uporabniki s posebnimi potrebami; knjižnice; izobraževalni programi; strokovna usposobljenost; bibliotekarji; student; študenti; Slovenia; Slovenija